Clinicopathological characteristics and prognosis of adolescents and young adults with gastric cancer after gastrectomy: a propensity score matching analysis - Chu, Hongwu; Chen, Xiaoyan; Liu, Xin; Deng, Cuncan; Bi, Bo; He, Yulong; Huo, Mingyu; Zhang, Changhua (Frontiers in Oncology, 2023)
Background: Gastric cancer (GC) among adolescents and young adults (AYAs, aged 15-39 years) has limited data on clinicopathological characteristics and prognosis. This study aimed to compare the clinicopathological characteristics, perioperative outcomes, and long-term outcomes of AYAs and older adults (OAs, aged > 39 years) with GC who underwent curative gastrectomy.Methods: From January 1994 to June 2019, patients with GC undergoing curative gastrectomy were enrolled and divided into AYA group and OA group. The clinicopathological characteristics, treatment variables, perioperative outcomes and long-term outcomes were compared between the two groups, both before and after propensity score matching (PSM).Results: AYAs had fewer comorbid conditions and were more likely to be females, have normal carcinoembryonic antigen (CEA) levels, poorly differentiated tumors with perineural invasion, and receive adjuvant chemotherapy. AYA patients had lower incidence of postoperative complications and shorter length of postoperative hospital stay than OA patients. No significant differences in postoperative 30-day or 90-day mortality were observed between AYAs and OAs, both before and after PSM. In the entire cohort, AYAs had similar median overall survival (OS) to OAs. However, in the PSM cohort, AYAs had significantly shorter median OS. Young age (15-39 years) was an independent risk factor for OS in GC patients following gastrectomy.The clinicopathological characteristics were significantly different between AYA and OA patients with GC. AYA patients with GC had worse long-term prognosis than OA patients, and young age was an independent risk factor for OS in GC patients following gastrectomy.